Association of spicy food consumption with colorectal polyp and adenoma prevalence: findings from the Lanxi Pre-Colorectal Cancer Cohort (LP3C) - Hu, Peiling; Yan, Xinran; Hu, Xiaodong; Lin, Xunan; Zhao, Jing; Pan, Fuzhen; Liu, Xiaohui; Ye, Hao; Zhuang, Pan; Zhang, Yu; Zheng, Weifang; Jiao, Jingjing (Frontiers in Nutrition, 2025)
ObjectiveThis study examined the relationship between habitual spicy food intake and the risk of colorectal polyps and adenomas in a high-risk Chinese cohort.MethodsWe analyzed baseline data from 14,907 participants aged 40–80 years enrolled in the Lanxi Precolorectal Cancer Cohort (LP3C) between March 2018 and December 2022. Dietary intake was assessed using a validated, single-administered baseline food frequency questionnaire (FFQ), with food intake frequency categorized into quartiles for analysis. Endoscopically confirmed colorectal lesions were histologically characterized. Multivariable-adjusted logistic regression models (adjusted for age, sex, body mass index (BMI), smoking, etc.) quantified lesion risks across spicy food consumption quartiles, with restricted cubic spline analyses evaluating non-linear exposure-response relationships.ResultsAmong 4,797 identified colorectal polyps and 2,607 adenomas, escalating spicy food intake exhibited a significant positive association with polyp risk (quartile 4 vs. quartile 1 OR: 1.24, 95% CI 1.13–1.37; P for trend < 0.001), contrasting with non-significant adenoma associations (quartile 4 vs. quartile 1 OR: 1.07, 95% CI 0.94–1.20; P for trend = 0.146), which was not clinically meaningful. Restricted cubic spline modeling revealed a non-linear relationship between spicy food intake and polyp risk (P for non-linearity < 0.001), characterized by initial risk elevation followed by a slight decrease with increasing consumption levels. Stratified analyses demonstrated consistent positive associations for polyp subgroups including small (≤5 mm) and large (>5 mm) lesions, single and multiple presentations, Yamada type classifications (≤II or ≥III), and both distal/proximal colonic locations (all P for trend ≤ 0.014).ConclusionOur findings identify spicy food consumption as an independent dietary correlate of colorectal polyp formation in high-risk Chinese adults, with differential risk patterns across lesion subtypes and anatomical sites. These novel epidemiological findings suggest that limiting spicy food consumption may reduce polyp risk in populations at high risk of colorectal cancer.